Use of Technology Among Older People in Times of Social Distancing due to COVID-19 - Corrêa Borges, Gabriel (2024)
The research aimed to analyze the situation of social isolation through the LUBBEN Brief Scale of Social Networks and to identify the use of technology among elderly people aged 60 or over. This is a study with a quantitative, cross-sectional and analytical approach. Data collection consisted of a sociodemographic questionnaire, applied to elderly people, seeking their profile, use of technology and perceptions of social isolation using the Lubben Scale. The sample consisted of 230 elderly people, with 199 people (86.5%) claiming to use the internet to access some social network and 130 (56.5%) reporting difficulties in accessing the internet. As for frequency, 69.10% use the internet frequently, while 23.5% use it a few times. With regard to social isolation, the frequency measured using the Brief Social Networking Scale of Lubben is only 12%, presenting themselves as socially isolated, while 88% of people showed no social isolation. The use of digital technologies by elderly people has a positive role in overcoming negative feelings such as isolation observed in times of social distancing due to Covid-19, with the need for more inclusion and digital literacy of these people.